(3GdTeSjg GdefUhQjIs - (3MSf Hf fhM GdbeQj, CHh efUhQ,fMh (B380 (3g`s ((3YeQ Hf YHO Gddg s)
(3ChdgG (B:s
(3HYO GdMeO ddg (B: (3bGd GdTjN GdMcje CHh efUhQ de CRd efP UHGFi YbdJ HMH GdYdhe GdWHjYjI s
(3BNQgG (B:s
(3EPG cGf jhLO Pdc ai cd ecGf hCcGfJ GdMGLI EdjgG Jbd hajeG CJjJ Hg ef Jdc GdfSN Zfjg Yf GdQLhY HMeO Gddg s
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B224 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B299s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B424 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdWH (B- (3bSe GdcJGH GdChd (B- (3U (B122 s
Keywords: (3GdWHs